PENGARUH CITRA KULINER TRADISIONAL KHAS KAILI TERHADAP KEPUTUSAN PEMBELIAN PADA KAWASAN WISATA ANJUNGAN PANTAI TALISE DI KOTA PALU - Rifki., Moh. (Fakultas Ekonomi Universitas Tadulako, 2019)
The Central Sulawesi government is now starting to increase tourism potential in each of its regions to increase local revenue. In tourism the most spent expenditure is food and beverage where there are several places that tourists can visit to enjoy culinary tourism, one of which is the Talise Beach Pavilion tourist area that provides traditional culinary tours. This study aims to find out and analyze the influence of traditional traditional culinary imagery on purchasing decisions in the tourist area of Talise Beach Pavilion. This type of research is quantitative. Medote research is descriptive causal. The sample used is as many as 60 respondents with the sampling form using incidental sampling techniques. Data analysis method used is multiple linear regression analysis method. The results of this study indicate that the dimensions of the image which consist of strength, uniqueness, and excellence simultaneously have a significant effect on purchasing decisions with a value of Sig F = 0,000 and have a large influence of 40.6%. As well as partially the image dimensions have a significant effect on purchasing decisions